The Importance of Civic Education Learning Using Canva Media in Developing Students' Critical Thinking Skills: Pentingnya Pembelajaran Pendidikan Kewarganegaraan Menggunakan Media Canva Dalam Pembentukan Keterampilan Berpikir Kritis Siswa - Akbar Hajuan, Muhammad (Citizenship Education, Faculty of Education, Jambi University, 2025)
The aim of this research is to form citizenship skills in learning Citizenship Education using the Canva application at SMP Negeri 1 Kauman Nganjuk. Canva learning media in Citizenship Education learning in improving citizenship skills (students' critical thinking skills) through Canva media in collaboration with interesting and fun learning. In this study, researchers investigated the cause and effect relationship of using Canva media in learning Citizenship Education to improve students' skills at SMP Negeri 1 Kauman Nganjuk. This research focuses on how to design Canva media in Citizenship Education learning. This study used a non-equivalent control group pretest and posttest design. As a sampling strategy. And the data collection technique is through questionnaire-based non-tests, as well as initial pretest and final posttest testing. The results of this research are that students are able to design learning media using Canva so that students' existing skills increase to increase their insight and critical thinking skills in Citizenship Education learning. Students are actively involved in designing PPT image media flayers and also video editors so that learning outcomes look useful. Students appear active in participating in citizenship education learning compared to not using learning media.